Pengaruh Arang Aktif Bidara dalam Menunda Kematangan Buah Klimakterik Tomat (Solanum lycopersicum) - Rizaldi, Lalu Heri; Hestiningsih, Ni Komang (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Tomato (Solanum lycopersicum) is classified as a climacteric fruit that is easily damaged, especially during the storage and shipping process, so proper postharvest management is needed. Postharvest management of climacteric fruit can be overcome by inhibiting the process of respiration and transpiration using activated charcoal. Activated charcoal works by absorbing ethylene gas during the respiration process. This study aims to analyze the use of bidara activated charcoal variations as an inhibitor of tomato ripeness and to examine changes in fruit quality during the 10day storage. The research used One Way Anova analysis with one factor of variation of activated charcoal with control treatment, 1gr, 3gr, and 5gr. Parameters tested were weight loss, Total Soluble Solid, and vitamin C. The use of bidara activated charcoal on tomatoes got the best results in the 5gr treatment with a weight loss value of 0.46%, 0.10 obrix total dissolved solids, and 18.93% vitamin C. Bidara activated charcoal had an effect on weight loss and total soluble solids but had no effect on vitamin C content. Bidara wood activated charcoal can be developed into an absorbent material for tomatoes.